Material and Doping Dependence of the Nodal and Antinodal Dispersion Renormalizations in Single- and Multilayer Cuprates. (28th February 2010) - Johnston, S.; Lee, W. S.; Chen, Y.; Nowadnick, E. A.; Moritz, B.; Shen, Z.-X.; Devereaux, T. P.
Abstract : We present a review of bosonic renormalization effects on electronic carriers observed from angle-resolved photoemission spectra in the cuprates. Specifically, we discuss the viewpoint that these renormalizations represent coupling of the electrons to the lattice and review how materials dependence, such as the number of CuO 2 layers, and doping dependence can be understood straightforwardly in terms of several aspects of electron-phonon coupling in layered correlated materials.